Pre-harvest Weeds of a Wheat Field at Biratnagar, Nepal (Our Nature, 2014)
Sixty eight species of weeds belonging to 22 families and 59 genera were recorded from a wheat field at Biratnagar during the pre-harvest condition. Based on species prevalence the dominant weed families were Asteraceae (17 species), Poaceae (13 species) and Fabaceae (6 species). Anagallis arvensis, Crepis japonica, Grangea maderaspatana, Polygonum plebeium were abundant and Fumaria indica, Leucas lavandulifilia, Rumex dentatus, Vicia angustifolia, V. hirsuta and V. tetrasperma were common species of weeds. DOI: http://dx.doi.org/10.3126/on.v11i2.9597 Our Nature 2013, 11(2): 187-191